Thermal buckling and vibration of laminated composite plates with temperature dependent properties by an asymptotic numerical method. Issue 1 (2nd January 2020) - Abdoun, Farah; Azrar, Lahcen
Abstract: The objective of this work is the elaboration of analytical and numerical procedures to investigate thermal buckling and vibration analyses of composite plates with thermal dependent material properties. Based on the homotopy and an asymptotic numerical method, a mathematical formulation that may account for various temperature dependent models is elaborated. Power series expansions of the displacement and the temperature are developed, and the finite element method is used for numerical solution. The effects of temperature dependent properties, structural geometry and boundary conditions on the thermal buckling and vibration are analyzed.